Light Zone City: Light Planning in the Urban Context - van Santen, Christa (Birkhäuser, 2006)
In this book, the author embodies her many years of experience as a practitioner and teacher of lighting design. She articulates basic planning rules for the outdoor lighting of buildings, traffic routes, and squares, and presents and elucidates new artificial lighting systems and outdoor lamps with the help of examples.